2015
DOI: 10.1080/17457300.2015.1047865
|View full text |Cite
|
Sign up to set email alerts
|

Safety concerns related to modular/prefabricated building construction

Abstract: The US construction industry annually experiences a relatively high rate of fatalities and injuries; therefore, improving safety practices should be considered a top priority for this industry. Modular/prefabricated building construction is a construction strategy that involves manufacturing of the whole building or some of its components off-site. This research focuses on the safety performance of the modular/prefabricated building construction sector during both manufacturing and on-site processes. This safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 2 publications
(2 reference statements)
0
63
0
Order By: Relevance
“…Insufficient radius of crane operation and insufficient lifting capacity of lifting machinery are critical issues, especially in volumetric prefabricated buildings [42]. There are safety risks during the construction process such as failure of lifting connection and lifting operation error [43].…”
Section: Construction Stagementioning
confidence: 99%
“…Insufficient radius of crane operation and insufficient lifting capacity of lifting machinery are critical issues, especially in volumetric prefabricated buildings [42]. There are safety risks during the construction process such as failure of lifting connection and lifting operation error [43].…”
Section: Construction Stagementioning
confidence: 99%
“…Among the site works of HMB, module installation ( Figure 1) is one of the most critical activities to ensure the successful project delivery (Gibb 1999). Module installation usually occupies heavy-duty tower cranes which is in the critical path of the construction programme (Olearczyk et al 2014), and it always concerns much of the construction safety (Fard et al 2017).…”
Section: Module Installation Process Analysismentioning
confidence: 99%
“…Modular building includes assembling the entire building or some parts off-site. The study discovered 125 mishaps identified with pre-assembled fabricating development with the most frequent types of harm are "crack" and "fall" (Fard et al, 2015).…”
Section: Modular Building Structurementioning
confidence: 99%